Japanese festivals : - Sakurai, Tokutaro (International Society for Educational Information Press, 1970)
In Japan, as in most other countries of the world, festivals have come to assume more and more importance as tourist attractions. But the interested visitor to Japan at first can have no concept of the wealth and unbelievable variety of festivals and observances to be found throughout the land.